Acute Heart Failure and Non-Ischemic Cardiomyopathies: A Comprehensive Review and Critical Appraisal - Lina Manzi; Federica Buongiorno; Viviana Narciso; Domenico Florimonte; Imma Forzano; Domenico Simone Castiello; Luca Sperandeo; Roberta Paolillo; Nicola Verde; Alessandra Spinelli; Stefano Cristiano; Marisa Avvedimento; et al. (Diagnostics)
Acute heart failure (AHF) is a complex clinical syndrome characterized by the rapid or gradual onset of symptoms and/or signs of heart failure (HF), leading to an unplanned hospital admission or an emergency department visit. AHF is the leading cause of hospitalization in patients over 65 years, thus significantly impacting public health care. However, its prognosis remains poor with high rates of mortality and rehospitalization. Many pre-existing cardiac conditions can lead to AHF, but it can also arise de novo due to acute events. Therefore, understanding AHF etiology could improve patient management and outcomes. Cardiomyopathies (CMPs) are a heterogeneous group of heart muscle diseases, including dilated cardiomyopathy (DCM), hypertrophic cardiomyopathy (HCM), restrictive cardiomyopathy (RCM), non-dilated cardiomyopathy (NDLVC), and arrhythmogenic right ventricular cardiomyopathy (ARVC), that frequently present with HF. Patients with CMPs are under-represented in AHF studies compared to other etiologies, and therefore therapeutic responses and prognoses remain unknown. In DCM, AHF represents the most frequent cause of death despite treatment improvements. Additionally, DCM is the first indication for heart transplant (HT) among young and middle-aged adults. In HCM, the progression to AHF is rare and more frequent in patients with concomitant severe left ventricle (LV) obstruction and hypertrophy or severe LV systolic dysfunction. HF is the natural evolution of patients with RCM and HF is associated with poor outcomes irrespective of RCM etiology. Furthermore, while the occurrence of AHF is rare among patients with ARVC, this condition in NDLVC patients is currently unknown. In this manuscript, we assessed the available evidence on AHF in patients with CMPs. Data on clinical presentation, therapeutic management, and clinical outcomes according to specific CMPs are limited. Future HF studies assessing the clinical presentation, treatment, and prognosis of specific CMPs are warranted.